Ketersediaan Koleksi Perpustakaan sebagai Faktor Penentu Minat Baca Mahasiswa di IAKN Tarutung - Simangunsong, Citra Octavia (LPPM-Institut Agama kristen Negeri Tarutung, 2024)
The aim of this research is to analyze the influence of the availability of book collections on the reading interest of undergraduate students in the MPK study program at the IAKN Tarutung library. The method used in this research is a quantitative method with inferential statistical analysis. The population is all undergraduate students from the MPK study program at IAKN Tarutung in 2024 with a total of 287 students and a sample of 71 people was determined using random sampling techniques. Data was collected using a closed questionnaire with 30 items. The results of the data analysis show that there is a positive and significant influence of the availability of collections on the reading interest of undergraduate students in the MPK study program at IAKN Tarutung in 2024, proven through the following data analysis: 1) Test the analysis requirements: a) test the positive influence obtained by the value rxy = 0.560 > rtable(=0.05,n=71) = 0.235, thus it is known that there is a positive influence between variable X and variable Y. b) Test the significant relationship obtained by the value tcount= 5.615 > ttable(=0.05,dk=n-2=69)= 2.000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 31.4%. 3) Test the hypothesis using the F test, obtained Fcount > Ftable, namely 31.523 > 4.00. Thus Ha is accepted and H0 is rejected.